Production Unit Management at SMK Negeri 1 Gelumbang to Respond to Industry 4.0 Challenges - Junainah, Junainah; Harapan, Edi; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2022)
This study intends to describe and assess the production unit management of SMK Negeri 1 Gelumbang, including implementation, monitoring, and evaluation. Descriptive qualitative research is what this study is. procedures for gathering data through observation, interviews, and documentation, followed by methods for analyzing data that include data reduction, data presentation, and conclusion-drawing. According to the study’s overall findings, management has been successfully implemented at SMK Negeri 1 Gelumbang’s production unit. Beginning with the planning, organizing, carrying out, monitoring, and evaluation of what has been accomplished and identifying the issues that are impeding the implementation of the Production Unit. Product marketing from each production unit of knowledge competence is also fairly good, and they are beginning to use digital marketing through social media, including Facebook, Instagram, and Whatsapp, which can be accessed both inside and outside the educational setting.